P119 Co-morbid insomnia is associated with worse health, and lower CPAP recommendation rates and nightly use in people with sleep apnoea. (9th November 2022) - Tan, D; Appleton, S; Chai-Coetzer, C; Lovato, N; Vakulin, A; Adams, R; Grivell, N; Sweetman, A
Abstract: Introduction: Co-morbid insomnia and sleep apnoea (COMISA) is associated with poor health and reduced adherence to continuous positive airway pressure (CPAP) therapy in sleep clinic samples. However, health and treatment correlates of COMISA in community-based samples of obstructive sleep apnoea (OSA) are poorly described. Methods: Australian adults previously diagnosed with OSA were surveyed online. COMISA was defined as co-morbid OSA and nocturnal insomnia symptoms (difficulties falling asleep, maintaining sleep, and/or early morning awakenings at least a few nights a week over the past month). Logistic regression and ANCOVAs determined associations of COMISA with medical conditions and general health, controlling for age, gender, and body mass index. Treatment recommendation rates and average nightly use were compared between those with COMISA versus OSA-alone. Results: Among 412 participants (54.6% male, mean age 58.5 [SD=13.9] years), 74.8% had COMISA. Compared to OSA-alone, COMISA was associated with higher rates of fair/poor general health (60.4% versus 46.6%, p=0.010), lower EQ-5D overall health (mean difference 7.55 [SD=2.73], p=0.010), and greater rates of depression diagnoses (56.3% versus 28.0%, p<0.001), which persisted after adjustment for covariates. People with COMISA reported lower rates of CPAP therapy recommendation (82.8%, versus 95.2%, p=0.002), and nightly use (mean difference 0.54 [SD=0.13] hours/night, p<0.001), and greater rates of upper-airway surgery recommendations (14%, versus 2.9%, p=0.002) and completion (13%, versus 1.9%, p=0.001). Conclusions: COMISA was associated with worse health, depression, lower CPAP recommendations and use, and greater upper-airway surgery compared to those with OSA-alone.